IDEOLOGICAL CHANGE OF ULU AMBEK DANCE IN PARIAMAN COMMUNITY, WEST SUMATRA - -, Yulinis (E-Journal of Cultural Studies, 2013)
ABSTRACT This present study discussed the ideological change of ulum ambek (UA) dance resulting from the impact of globalization. This is indicated by the fact that the young generation is getting less interested in performing UA dance in Pariaman. This study, in which qualitative, critical, holistic, and emancipatoric approaches were used, analyzed the form of, the factor contributing to, the meaning and the impact of the ideological change of UA dance in Pariaman community. The relevant theories used are the theory of ideology, the theory of hegemony, and the theory of semiotics. The data were collected using observation, interview, and documentary techniques, and were qualitatively and interpretatively analyzed. The results of the study showed that the form of the ideological change of UA dance performed in Pariaman was related to the ideology of what is referred to as penghulu (Muslim leader). The values of life such as the learning of good manners or better known as batarik (regulations for conduct) were expressed through UA dance. The meanings of UA dance included knowledge, values, and the belief adhered to in the Pariaman culture. The impact of the ideological change of UA dance was related to the people’s welfare, solidarity, and the balance between human and the nature. The value of tageh constituted the aesthetic meaning of UA dance and the value of creativity constituted the value of creative development and the value of ideological development. Theoretically, this present study revealed that the ideological meaning of UA dance in Pariaman West Sumatra included the aesthetic value referred to as tageh which was related to the aesthetics of UA dance performance and the bataratik value was related to the ideology of the Pariaman community, apart from the appearance of creativity related to the development of UA dance.
Keywords: Ulu Ambek dance, Pariaman